2015
DOI: 10.1128/aem.00590-15
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Gamma Radiation on Sediment Microbial Processes

Abstract: cMicrobial communities have the potential to control the biogeochemical fate of some radionuclides in contaminated land scenarios or in the vicinity of a geological repository for radioactive waste. However, there have been few studies of ionizing radiation effects on microbial communities in sediment systems. Here, acetate and lactate amended sediment microcosms irradiated with gamma radiation at 0.5 or 30 Gy h ؊1 for 8 weeks all displayed NO 3 ؊ and Fe(III) reduction, although the rate of Fe(III) reduction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 64 publications
3
13
0
1
Order By: Relevance
“…At the family level, significantly dominant sequences obtained from contaminated sites are Moraxellaceae (under Proteobacteria), Chitinophagaceae (Bacteroidetes), unclassified Candidatus Azambacteria (Parcubacteria), unclassified Candidatus Moranbacteria (Parcubacteria), unclassified Candidatus Collierbacteria (Microgenomates), and unclassified Gammaproteobacteria (Proteobacteria), while Comamonadaceae (Proteobacteria), Rhodocyclaceae (Proteobacteria), Nitrospirales Incertae Sedis (Nitrospirae), cvE6 (Chlamydiae), unclassified Woesearchaeota (DHVEG-6) (Woesearchaeota), and Holophagaceae (Acidobacteria) are abundant in control sites (t-test; p < 0.05). The bacterial assemblages mentioned above were found to be dominated in contaminated radon water and were reported to be abundantly inhabitant in radiation and chemolithotrophic environments (Poirel et al, 2008;Brown et al, 2015;Rao et al, 2016;Danczak et al, 2017), thus supporting our finding. On the other side, dominant families present in the control water were generally reported to be present in natural soil and drinking water (Li et al, 2016;Deja-Sikora et al, 2019).…”
Section: Microbial Community Comparison Between Contaminated and Non-contaminated Sitessupporting
confidence: 88%
See 2 more Smart Citations
“…At the family level, significantly dominant sequences obtained from contaminated sites are Moraxellaceae (under Proteobacteria), Chitinophagaceae (Bacteroidetes), unclassified Candidatus Azambacteria (Parcubacteria), unclassified Candidatus Moranbacteria (Parcubacteria), unclassified Candidatus Collierbacteria (Microgenomates), and unclassified Gammaproteobacteria (Proteobacteria), while Comamonadaceae (Proteobacteria), Rhodocyclaceae (Proteobacteria), Nitrospirales Incertae Sedis (Nitrospirae), cvE6 (Chlamydiae), unclassified Woesearchaeota (DHVEG-6) (Woesearchaeota), and Holophagaceae (Acidobacteria) are abundant in control sites (t-test; p < 0.05). The bacterial assemblages mentioned above were found to be dominated in contaminated radon water and were reported to be abundantly inhabitant in radiation and chemolithotrophic environments (Poirel et al, 2008;Brown et al, 2015;Rao et al, 2016;Danczak et al, 2017), thus supporting our finding. On the other side, dominant families present in the control water were generally reported to be present in natural soil and drinking water (Li et al, 2016;Deja-Sikora et al, 2019).…”
Section: Microbial Community Comparison Between Contaminated and Non-contaminated Sitessupporting
confidence: 88%
“…Nitrospira is a chemolithotrophic nitrite-oxidizing bacterium that shows the highest phylogenetic diversity and widest environmental distribution but is majorly found in fresh water and salt water (Daims et al, 2016) probably because of its reduced survival and adaptation strategies with a higher radionuclide-contaminated water. Meanwhile, Bacteroidetes was previously reported to be dominant in uranium-contaminated soils and γ-irradiated sediments (Brown et al, 2015;Yan et al, 2016), so it must have better survival strategies in such harsh environments. It is also reported that Bacteroidetes utilizes the catalase gene in order to show a resistance phenotype against oxidative stress (Rocha et al, 1996).…”
Section: Microbial Community Comparison Between Contaminated and Non-contaminated Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“… 2014 ) and also stimulated Fe(III) reduction in more complex sediment microcosms (Brown et al . 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Předběžné výpočty pro český koncept udávají dávkový příkon na povrchu UOS pod 0,4 Gy h -1 [39]. Např.v práci Brown et al [40] se zabývali vlivem dvou různých dávkových příkonů gama záření 30 Gy h -1 a 0.5 Gy h -1 po dobu 8 týdnů na životnost různých typů bakterií. V prostředí bez organických nutrientů nebyl pozorován žádný vliv IZ na životnost bakterií, naopak Geothrix fermentans a Geobacter sp.…”
Section: Mikrobiální Koroze V Hlubinném úLožištiunclassified